Effect of Macroeconomic Variables on Stock Market Performance of SAARC Countries - Ullah, Golam Mohammad Wali; Islam, Ashraful; Alam, Md. Sohan; Khan, Md. Kanon (Asian Economic and Financial Review, 2017)
Stock market is one of the most widely followed markets in the world with a horde of transactions facilitated every day. Thus, not surprisingly a plethora of research has been dedicated to understanding the nature of these markets and what factors affect their movements and performance in general. Several studies have postulated that macroeconomic variables do tend to significantly affect stock market performance, while other studies found inconclusive relation at best. It is also worth noting that most of these studies were conducted on developed markets and rarely touched on the developing markets. On this background, the objective of this study is to examine the significance of macroeconomic variables in effecting stock market performance of SAARC countries using the OLS multiple regression Model. We have used annual data for the period 2005-2015. The findings of the study showed that macroeconomic variables i.e. exchange rate, foreign currency reserve and interest rate are all statistically significant in affecting stock market performance of SAARC countries. Whereas, inflation and money do not have a significant relationship in affecting stock market performance.